A phylogenetically conserved hnRNP type A/B protein from squid brain. (23rd March 2019) - Lopes, Gabriel Sarti; Lico, Diego Torrecillas Paula; Silva-Rocha, Rafael; de Oliveira, Renata Rocha; Sebollela, Adriano; Paçó-Larson, Maria Luisa; Larson, Roy Edward
Highlights: Molecular structure and function of hnRNPA/B class of RNA-binding proteins are phylogenetically conserved. The propensity of squid hnRNPA/B-like Protein 2 stably dimerize may gives clues about the p65 protein. The corresponding M9 region of squid hnRNPA/B-like Protein 2 clearly has a role on its subcellular distribution. Stress induced cytoplasmic granules of squid hnRNPA/B-like Protein 2 may indicate a role of squid protein in stress response. Abstract: Eukaryotic mRNA precursors are co-transcriptionally assembled into ribonucleoprotein complexes. Heterogeneous nuclear ribonucleoprotein (hnRNP) complexes are involved in mRNA translocation, stability, subcellular localization and regulation of mRNA translation. About 20 major classes of hnRNPs have been identified in mammals. In a previous work, we characterized a novel, strongly-basic, RNA-binding protein (p65) in presynaptic terminals of squid neurons presenting homology with human hnRNPA/B type proteins, likely involved in local mRNA processing. We have identified and sequenced two hnRNPA/B-like proteins associated with tissue purified squid p65: Protein 1 (36.3 kDa, IP 7.1) and Protein 2 (37.6 kDa, IP 8.9). In the present work we generated an in silico, tridimensional, structural model of squid hnRNPA/B-like Protein 2, which showed highly conserved secondary and tertiary structure of RNA recognition motifs with human hnRNPA1 protein, as well as illustrated the potential for squid Protein 2 stable homodimerization. This was supported by biophysical measurements of bacterially expressed, recombinant protein. In addition, we induced expression of squid hnRNPA/B-like Protein 2 in human neuroblastoma cells (SH-SY5Y) and observed an exclusively nuclear localization, which depended on an intact C-terminal amino acid sequence and which relocated to cytoplasm particles containing PABP when the cells were challenged with sorbitol, suggesting an involvement with stress granule function.